2012
DOI: 10.1038/pcan.2012.12
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone recovery in the off-treatment time in prostate cancer patients undergoing intermittent androgen deprivation therapy

Abstract: The prerequisite of an IAD treatment is the testosterone recovery during off-treatment periods. In this study, in patients with PSA relapse after radical prostatectomy, a real achievement of intermittent castration with normalisation of testosterone levels during off-treatment periods could be confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 18 publications
1
54
0
2
Order By: Relevance
“…In addition, when androgen blockade is used intermittently, a minority of patients can have recovery of testosterone and have no progression [10,41]. These findings mirror similar observations in postmenopausal breast cancer treated with oestrogen therapy, as the response rate was higher in those over the age of 60 [42].…”
Section: Discussionsupporting
confidence: 78%
“…In addition, when androgen blockade is used intermittently, a minority of patients can have recovery of testosterone and have no progression [10,41]. These findings mirror similar observations in postmenopausal breast cancer treated with oestrogen therapy, as the response rate was higher in those over the age of 60 [42].…”
Section: Discussionsupporting
confidence: 78%
“…Evaluation of OS was the primary endpoint in 4 studies [8-10,50,55,58] and TTP or time to androgen-independent was the primary endpoint in 7 studies [1,11,12,44-47,50-54,56,57] (Table 2). Five studies [1,8-10,44-47,55,58] were designed to evaluate the non-inferiority of IAD compared to CAD (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…This includes intermittent treatment. 5,6 Most phase 2 studies have shown that intermittent ADT regimens decrease adverse events and improve QoL during offtherapy periods, with promising tolerability profiles. Also, early phase 3 results show a better tolerability profile and QoL with intermittent ADT than with continuous treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Intermittent androgen suppression may reduce the side effects of therapy during off-treatment periods. 6 The resulting hypogonadism due to ADT may leads to adverse results, such as osteoporosis, unfavourable body composition (increase in body mass index, increased fat mass, reduced lean body mass and muscle strength), sexual dysfunction, and reduced quality of life. Recent studies suggest male hypogonadism is an independent risk factor for the development of metabolic syndrome and diabetes.…”
Section: Introductionmentioning
confidence: 99%